PENGARUH PERSEPSI NEGARA ASAL TERHADAP NIAT BELI ULANG DIMEDIASI OLEH EKUITAS MEREK - Putra, I Komang Satria Warla; Setiawan, Putu Yudi; Respati, Ni Nyoman Rsi (E-Jurnal Manajemen; Vol 7 No 7 (2018)DO - 10.24843/EJMUNUD.2018.v07.i07.p19, 2018)
A customer in determining the intention to repurchase is determined by various factors, such as the image of the home country and the equity of a brand. The purpose of this study was to determine the effect of the perception of the country of origin on repurchase intention mediated by brand equity. This research was conducted on Xiaomi brand smartphone customers in Denpasar City. The number of samples taken as many as 120 people, with the method of non-probability sampling, especially purposive sampling Data collection is done through a questionnaire. The collected data is measured by Likert scale with scale 1-5. The analysis technique used is Partial Least Square (PLS). Based on the results of the analysis shows that all hypotheses are accepted. The country of origin has a positive and significant impact on brand equity. Brand equity has a positive and significant effect on the repurchase intention, the country of origin has a positive and significant impact on the repurchase intention and the brand equity is able to mediate the influence of the country of origin on the intention to repurchase the Xiaomi brand smartphone in Denpasar City. Keywords : Country of origin, brand equity, repurchase intention, Xiaomi smartphone